Analysis of the defensive process in football Influence of contextual factors on the ball recovery actions (Analysis of Lithuanian U19 Elite Football Team) - Casaleiro, Ricardo Fernando Lopes (2021)
In football, recovering the ball possession is one of the main purposes of the defensive phase and simultaneously it is also the first stage of the attacking phase. Identifying how and where the ball is regained by taking into consideration contextual variables is a key determinant to the understanding of the defensive behavior of a team and, consequently, can also be important information to develop specific drills in training sessions. The present study aimed to identify the defensive actions and behaviors related to the moment of ball possession recovery taking into consideration different contextual variables. The sample of this study consisted of 1512 ball possession recoveries from 12 games of a U19 Elite Lithuanian Football team. The 1512 ball possession recoveries were analyzed according to the match status and period of the game. The data analysis was performed using descriptive statistics. The results showed that the most prominent zones to recover the ball possession are the offensive center midfield zone (OCMZ) and defensive center midfield zone (DCMZ). The offensive zones registered higher numbers of ball recoveries in the first period of the games, while the defensive zones registered an increase of the ball recoveries in the final periods of the game. Regarding the match status, the team tended to recover more balls when losing. Recovering the ball in higher zones of the pitch allowed the team to reach the goal. The results found showed that the frequency of ball possession recoveries depends on match status and period of the game. The performance indicators shots on target and goals were also influenced by the zones where the ball possession occurred. The coaching staff can benefit from knowing the current results in order to prepare the team's offensive and defensive structures.